Wildfires will intensify in the wildland-urban interface under near-term warming - Calum X. Cunningham; John T. Abatzoglou; Todd M. Ellis; Grant J. Williamson; David M. J. S. Bowman (Communications Earth & Environment)
Abstract Dangerous fire weather is increasing under climate change, but there is limited knowledge of how this will affect fire intensity, a critical determinant of the socioecological effects of wildfire. Here, we model relationships between satellite observations of fire radiative power (FRP) and contemporaneous fire weather index, and then we project how FRP is likely to change under near-term warming scenarios. The models project widespread growth in FRP, with increases expected across 88% of fire-prone areas worldwide under 1.5 °C warming. Projected increases in FRP were highest in the Mediterranean biome and Temperate Conifer Forest biome, and increases were twice as large under 2 °C warming compared to 1.5 °C. Disaster-prone areas of the wildland-urban interface saw an average of 3.6 times greater projected increases than non-disaster-prone areas, suggesting wildfire impacts will intensify most in regions already vulnerable to dangerous wildfires. These findings emphasise the urgent need to anticipate changes to fire behaviour and proactively manage wildland-urban ecosystems to reduce future fire intensity.